Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
The quadratic equation is;
y = 3x^2-7x + 5
when x = 4, y = 25
Step-by-step explanation:
Mathematically, the general form of a quadratic equation is;
y = ax^2 + bx + c
From the first point, we have that x = 0
Thus;
5 = a(0)^2 + b(0) +c
c = 5
Now, in a case when x is 2
3 = a(2)^2 + b(2) + 5
3 = 4a + 2b + 5
4a + 2b = -2 ••••••(i)
when x = 6
71 = a(6)^2 + b(6) + 5
66 = 36a + 6b ••••••(ii)
From equation i,
2b = -2-4a ••••(iii)
we can rewrite equation ii as
66 = 36a + 3(2b)
Substitute iii into ii
66 = 36a + 3(-2-4a)
66 = 36a - 6 - 12a
66 + 6 = 36a -12a
24a = 72
a = 72/24
a = 3
Recall;
2b = -2-4a
2b = -2-4(3)
2b = -2-12
2b = -14
b = -14/2
b = -7
So the quadratic equation would be;
y = 3x^2 -7x + 5
Now let us test;
when x = 10, y = 235
That would be:
y = 3(10)^2 -7(10) + 5
y = 300 - 70 + 5
y = 235
This shows that the derived quadratic equation is correct
Now, when x = 4; we have it that;
y = 3(4)^2 -7(4) + 5
y = 48 -28 + 5
y = 20 + 5 = 25
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.